Análise do comportamento de tubos geotêxteis para confinamento de rejeito fino de mineração por meio de modelagem numérica - Vitor Lara Silva (2019)
Mining tailings are waste generated in the ore beneficiation process and it should be disposed safely with small impact to the environment. The most common technology for disposal of this tailings is through dams, but, this alternative is encountering increasingly difficulties in licensing and operation because of the recente laws. As a new disposal alternative stands out the use of geotextile tubes to confine this material. Initially, the geotextile tubes were used in marine applications such as coastal protection. Later, they were used in the dewatering of waste, slurries and sludges. Recently, it has been applied in the dewatering of mine tailings. The tensions generated during the hydraulic disposal of the material in the geotextile tubes are determinant for the stability and security of the structure during the filling process. In addition, the determination of the shape of the geosynthetic tube aiming the stacking to optimize the space and increase the storage capacity of mine tailings is fundamental. The research covered an evaluation of the tensions and the shape during the filling of a geotextile tube by analytical methods and numerical modeling. The material inside the tube ware gold tailing. The methodology was based on the definition of the properties of the materials, woven geotextile and gold tailing, trough laboratory tests and existing data from the literature, existing field study from the literature to perform a retroanalysis, development of a numerical algorithm to apply on the selected analytical methods. Also, it was developed a numerical modeling using the software Abaqus version 6.14 and parametric analysis to verify the influence of the filling pressure, elastic módulos of the geotextile tube, the finite element that were more representative of the field condition during the numerical modeling and the suitability of the use of the program for simulations. The numerical algorithm developed in the work to solve the analytical methods indicated results consistent with those in the literature as well as with the results obtained from the field condition. The numerical modeling was also able to represent the behavior of the geotextile tube during the filling, the existing experiment from the literature as well as the existing data from the field study. It was notice that the choice of the type of the finit elemento used in numerical analysis is determinant for the behavior of the tensiles and strain in the geotextile tube. The filling pressure and the elastic influence the behavior of the cross section shape and tensions generated in the geotextile tube during the filling.